Detecting ecological impacts : concepts and applications in coastal habitats - Schmitt, Russell J.; Osenberg, Craig W. (Academic Press, 1996)
Detecting Ecological Impacts: Concepts and Applications in Coastal Habitats focuses on crucial aspects of detecting local and regional impacts that result from human activities. Detection and characterization of ecological impacts require scientific approaches that can reliably separate the effects of a specific anthropogenic activity from those of other processes. This fundamental goal is both technically and operationally challenging. Detecting Ecological Impacts is devoted to the conceptual and technical underpinnings that allow for reliable estimates of ecological effects caused by human a.